2016
DOI: 10.1186/s12933-016-0337-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pleiotropic effects among common genetic loci identified for cardio-metabolic traits in a Korean population

Abstract: BackgroundThe genetic contribution to complex diseases or traits, including cardio-metabolic traits, has been elucidated recently by large-scale genome-wide association studies. These genome-wide association studies have indicated that most pleiotropic loci contain genes associated with lipids. Clinically, lipid related abnormalities are strongly associated with other diseases such as type 2 diabetes, coronary artery disease and hypertension. The aim of this study was to evaluate the shared genetic background … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…However, the association of ACE2 SNPs with T2D and T2D related cardiovascular complications (e.g., hypertension and dyslipidemia) or events (e.g., ASCVD) in Chinese population are rarely reported. Theoretically, there may be common genetic basis between them [ 8 , 12 , 13 ] manifesting the characteristics of ethnic-specific genetic pleiotropy among cardio-metabolic traits [ 14 ]. In this study we investigated possible associations between ACE2 gene variation and cardiovascular risk in Uygur patients with type 2 diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%
“…However, the association of ACE2 SNPs with T2D and T2D related cardiovascular complications (e.g., hypertension and dyslipidemia) or events (e.g., ASCVD) in Chinese population are rarely reported. Theoretically, there may be common genetic basis between them [ 8 , 12 , 13 ] manifesting the characteristics of ethnic-specific genetic pleiotropy among cardio-metabolic traits [ 14 ]. In this study we investigated possible associations between ACE2 gene variation and cardiovascular risk in Uygur patients with type 2 diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%
“…In Table 1 , studies investigating common and rare variants in association with hypertension andBP phenotypes and through exome array approaches are listed. Most publications [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]; ( Table 1 ) took advantage of the Illumina HumanExome BeadChip (Exome Chip; Illumina, Inc., San Diego, CA, USA).…”
Section: Resultsmentioning
confidence: 99%
“…The combined associations of LIPC SNPs with insulin surrogate markers that based on both metabolic and adiposity status are noteworthy. Shared common variants have similarly been reported between lipid genes and glucose metabolism, inflammation, BMI, cardiometabolic traits, and coronary artery disease [ 20 , 40 , 44 46 ]. Pickrell et al [ 21 ] developed a method of detecting pairs of traits that exhibited an asymmetry in the effect sizes of associated variants, which is more consistent with a causal relationship between the traits and the authors indicated that an elevated BMI causally increases TG levels, but the reverse is not true.…”
Section: Discussionmentioning
confidence: 99%